The Effectiveness of Canva AI Media on Fifth-Grade Students' Science Literacy: A Pre-Experimental One-Group Pretest-Posttest Study at SD Negeri 3 Budakeling - I Gusti Gede Ariana; Made Adi Nugraha Tristaningrat; I Made Ari Winangun (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
The low science literacy of elementary school students is a serious concern amid 21st-century competency demands. PISA 2022 data placed Indonesia near the bottom in science literacy, while locally, fifth-grade students at SD Negeri 3 Budakeling demonstrated suboptimal science literacy achievement. This study aims to analyze the effectiveness of Canva AI as a supporting medium for science literacy in fifth-grade science learning at SD Negeri 3 Budakeling. A quantitative approach with a pre-experimental one group pretest-posttest design was employed. The research subjects consisted of 25 students. Data were collected through a science literacy test based on four indicators: observing phenomena, understanding science concepts, analyzing data, and communicating science. Data analysis employed descriptive statistics, paired t-test, and N-Gain. Results showed an increase in mean science literacy scores from 49.00 (pretest) to 79.25 (posttest), with an N-Gain value of 0.59 (medium category). The paired t-test yielded t = 14.73 (p < 0.001), confirming statistically significant improvement. These findings affirm that Canva AI, through its text-to-visual and AI-powered collaborative design features, effectively delivers concrete and engaging representations of scientific phenomena, meaningfully supporting elementary students' science literacy development